The Cuckoo's Calling - Galbraith, Robert, (MUlhollands Books, 2015)
"After losing his leg to a land mine in Afghanistan, Cormoran Strike is barely scraping by as a private investigator. Strike is down to one client, and creditors are calling. He has also just broken up with his longtime girlfriend and is living in his office. Then John Bristow walks through his door with an amazing story: his sister, the legendary supermodel Lula Landry, known to her friends as the Cuckoo, famously fell to her death a few months earlier. The police ruled it a suicide, but John refuses to believe that. The case plunges Strike into the world of multimillionaire beauties, rock-star boyfriends, and desperate designers, and it introduces him to every variety of pleasure, enticement, seduction, and delusion known to man."--Dust jacket.